1995
DOI: 10.1210/endo.136.12.7588333
|View full text |Cite
|
Sign up to set email alerts
|

Targeting simian virus 40 T antigen to the osteoclast in transgenic mice causes osteoclast tumors and transformation and apoptosis of osteoclasts.

Abstract: Osteoclasts are terminally differentiated cells that express tartrate-resistant acid phosphatase (TRAP) at a higher level than other normal cells. Therefore, in an attempt to develop immortalized osteoclasts, we produced two lines of transgenic mice in which expression of the simian virus 40 T antigen oncogene was targeted to osteoclasts using the TRAP gene promoter. Osteoclasts were increased in number in bones from both lines. More than 50% of them appeared morphologically transformed, 2-5% were mitotic, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 0 publications
4
30
0
Order By: Relevance
“…This is a possible explanation why there were a TRAP-positive structure with one TUNEL-positive nucleus, a TRAP-positive structure with one TUNEL-positive nucleus and one or two TUNEL-negative nuclei, and a TRAP-positive structure without any nucleus as observed by IHC in this study. Boyce et al (1995) reported that the intensity of TRAP staining in apoptotic osteoclasts was consistently stronger than that in viable osteoclasts. They considered that this intensity of TRAP in apoptotic osteoclasts might be a reflection of cytoplasmic condensation during cell death or could be due to increased production or decreased secretion of TRAP enzyme by the cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is a possible explanation why there were a TRAP-positive structure with one TUNEL-positive nucleus, a TRAP-positive structure with one TUNEL-positive nucleus and one or two TUNEL-negative nuclei, and a TRAP-positive structure without any nucleus as observed by IHC in this study. Boyce et al (1995) reported that the intensity of TRAP staining in apoptotic osteoclasts was consistently stronger than that in viable osteoclasts. They considered that this intensity of TRAP in apoptotic osteoclasts might be a reflection of cytoplasmic condensation during cell death or could be due to increased production or decreased secretion of TRAP enzyme by the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Decalcified sections were prepared and stained for TRAP activity, and morphologically viable and apoptotic osteoclasts were counted in the metaphyseal area and arthritic knee joints at the bone-pannus junction. Apoptotic osteoclasts were identified in TRAP-stained bone sections using standard morphologic criteria: cell shrinkage, nuclear condensation and fragmentation, cytoplasmic condensation and intense cytoplasmic TRAP staining, as described previously (13). It has been previously confirmed, using acridine orange staining and the TUNEL assay (4,13), that TRAPϩ osteoclasts with these appearances in culture plates and in tissue sections are apoptotic.…”
Section: Methodsmentioning
confidence: 99%
“…Macrophage colony-stimulating factor (M-CSF), a key survival factor for cells in the myeloid lineage, stimulates Bcl-xL expression (11,12). Osteoclasts generated from bone marrow cells of transgenic mice that overexpress Bcl-xL under the control of the tartrate-resistant acid phosphatase (TRAP) promoter are more resistant to serum withdrawal-induced cell death (13,14), demonstrating that Bcl-xL is involved in the control of osteoclast apoptosis.…”
mentioning
confidence: 99%
“…109 The generation of TRAP transgenic mice expressing the SV40 large T antigen, with or without the bcl-XL antiapoptotic gene, did not transform cells outside the osteoclast lineage. 14,54 The TRAP promoter has also been used to target overexpression of the c-fos gene to osteoclasts to generate a mouse model with some characteristics of Paget's disease. 11 Although Langerhans cells in the skin express TRAP, 49 the gene is also expressed in keratinocytes, and was shown to be elevated in the transgenic animals.…”
Section: Trap Expression At Extraskeletal Sitesmentioning
confidence: 99%